Direct methane solid oxide fuel cell anode catalyst layer material and preparation method and application thereof

By adding specific precursor materials to the SOFC anode material and calcining it in a reducing atmosphere, the problem of carbon deposits in Ni-based ceramic anode is solved, catalytic activity and durability are improved, and the performance of SOFC is improved.

CN119447335AInactive Publication Date: 2025-02-14NANJING TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411599501.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Solid oxide fuel cell (SOFC) When using methane as fuel, Ni-based ceramic anode will produce carbon deposits, affecting the battery performance and limiting the development of methane on SOFC.

Method used

The precursor material SrTi1-xRuxO3-δ with a specific molecular formula is calcined in a reducing atmosphere to obtain the catalytic layer material of the direct methane solid oxide fuel cell, and the nanometal particles are precipitated in situ to improve catalytic activity and durability.

Benefits of technology

It significantly improves the catalytic activity and durability of the catalytic layer material, reduces the production of carbon deposits, accelerates the methane reforming rate, and improves the operating stability and electrochemical performance of SOFC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447335A_ABST
    Figure CN119447335A_ABST
Patent Text Reader

Abstract

The invention relates to a direct methane solid oxide fuel cell anode catalyst layer material and a preparation method and application thereof, the direct methane solid oxide fuel cell anode catalyst layer material is prepared by calcining a precursor material in a reducing atmosphere, the molecular formula of the precursor material is SrTi1-xRuxO3-delta, in the formula, x is more than or equal to 0.05 and less than or equal to 0.15, and delta is oxygen vacancy content. A precursor material with a specific molecular formula is calcined in a reducing atmosphere, that is, nano metal particles are anchored on the surface of an anode perovskite oxide substrate of a solid oxide fuel cell (SOFC) through an in-situ precipitation strategy, and due to in-situ precipitation and close combination between two phases, the solid oxide fuel cell has high stability and sintering resistance, and can be applied to the field of fuel cell devices. The catalytic activity and durability of the catalytic layer material are obviously improved; the nano-particles separated out from the surface of the catalyst layer material increase active sites, stimulate the mechanism that lattice oxygen participates in methane reforming, accelerate the methane reforming rate and reduce the generation of carbon deposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid oxide fuel cells, and relates to a fuel cell anode catalyst layer material, and specifically to a direct methane solid oxide fuel cell anode catalyst layer material, and a preparation method and application thereof. Background Art

[0002] Solid oxide fuel cell (SOFC) belongs to the third generation of fuel cells. It is an all-solid-state chemical power generation device that directly converts the chemical energy stored in fuel and oxidant into electrical energy in an efficient and environmentally friendly manner at medium and high temperatures. It is generally believed that it will be a type of fuel cell that will be widely used in the future like proton exchange membrane fuel cells.

[0003] At present, the most commonly used fuel for solid oxide fuel cells (SOFCs) is hydrogen, but the main method of preparing hydrogen mainly relies on methods such as electrolysis of water and industrial reforming, resulting in a high preparation cost. In addition, hydrogen is also highly dangerous during transportation and storage. Methane is another gas fuel that can be used for solid oxide fuel cells (SOFCs). It is the main component of natural gas, renewable, and its products are pollution-free. However, when solid oxide fuel cells (SOFCs) use methane as fuel, Ni-based ceramic anodes will produce carbon deposits during the battery power generation process, thereby affecting the performance of the battery. This is an important issue that restricts the development of methane in solid oxide fuel cells (SOFCs).

[0004] The Chinese invention patent with application number 202311130071.9 discloses a solid oxide fuel cell anode electrocatalytic material and its preparation method and application, wherein the preparation method comprises the steps of: pouring SrCO3, Fe2O3 and TiO2 into a ball mill according to a preset stoichiometric ratio, using anhydrous ethanol as a solid phase mixing medium, and uniformly ball milling in the ball mill to obtain an initial mixed powder; placing the initial mixed powder in an oven for drying and then continuing to fully grind it with a mortar to obtain a secondary mixed powder; placing the secondary mixed powder in a muffle furnace, calcining at 1100-1300°C for 8-12h, and obtaining a solid oxide fuel cell anode electrocatalytic material. However, the anode electrocatalytic material is calcined in an air atmosphere, and Fe in the final product exists in the form of a 4+ / 3+ / 2+ redox pair, and there is still room for improvement in electrochemical performance. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a direct methane solid oxide fuel cell anode catalyst layer material to reduce the direct contact between the solid oxide fuel cell (SOFC) anode and methane, alleviate the carbon deposition problem, and improve the operating stability and electrochemical performance of the solid oxide fuel cell (SOFC).

[0006] In order to achieve the above technical objectives, the present invention provides a direct methane solid oxide fuel cell anode catalyst layer material, which is prepared by calcining a precursor material in a reducing atmosphere, wherein the molecular formula of the precursor material is SrTi 1-x Ru x O 3-δ , where 0.05≤x≤0.15 and δ is the oxygen vacancy content.

[0007] Optimally, the calcination temperature is 720-820°C and the calcination holding time is 2-5 h.

[0008] Furthermore, x is preferably 0.1.

[0009] Another object of the present invention is to provide a method for preparing the above-mentioned direct methane solid oxide fuel cell anode catalyst layer material, comprising the following steps: (a) weighing a soluble strontium salt, a soluble ruthenium salt and an organic titanium compound in a corresponding proportion according to the stoichiometric ratio of the molecular formula of the precursor material, adding them to water to dissolve and obtain a clear mixed solution; dissolving a complexing agent in an alkaline solution to form an alkaline regulating solution; then adding the alkaline regulating solution to the mixed solution, controlling the pH of the mixed solution to 9-10, and heating and stirring to obtain a gel-like substance; (b) drying the gel-like substance and subjecting it to high-temperature heat treatment to obtain a precursor material; (c) placing the precursor material in a reducing atmosphere to calcine to obtain the direct methane solid oxide fuel cell anode catalyst layer material.

[0010] Optimally, in step (a), the soluble strontium salt is Sr(NO3)2, the soluble ruthenium salt is RuCl3, the organic titanium compound is tetrabutyl titanate, the complexing agent is ethylenediaminetetraacetic acid, and the alkaline solution is 20-25% by mass of ammonia water.

[0011] Furthermore, in step (a), citric acid monohydrate is first added to water, the molar ratio of the citric acid monohydrate, ethylenediaminetetraacetic acid and total metal ions is 2:1:0.5-1.5, and the total metal ions are strontium ions and ruthenium ions.

[0012] Optimally, in step (b), the drying treatment temperature is 150-200° C. and the time is 5-10 hours.

[0013] Furthermore, in step (b), the high temperature heat treatment is performed at a temperature of 950-1000° C. and for a time of 5-8 hours.

[0014] Optimally, in step (c), the reducing atmosphere is a H2 atmosphere.

[0015] Another object of the present invention is to provide an application of the above-mentioned direct methane solid oxide fuel cell anode catalyst layer material, which is used as the catalyst layer on the anode side of the direct methane solid oxide fuel cell.

[0016] The direct methane solid oxide fuel cell anode catalyst layer material of the present invention is prepared by calcining a precursor material of a specific molecular formula in a reducing atmosphere, i.e., by an in-situ precipitation strategy, "anchoring" nano metal particles on the surface of an anode perovskite oxide substrate of a solid oxide fuel cell (SOFC). Due to the in-situ precipitation, the two phases are tightly combined, have high stability and sintering resistance, and significantly improve the catalytic activity and durability of the catalyst layer material; the nano particles precipitated on the surface of the catalyst layer material increase the active sites, stimulate the mechanism of lattice oxygen participating in the reforming of methane, accelerate the methane reforming rate, and reduce the generation of carbon deposits.

[0017] The method for preparing the direct methane solid oxide fuel cell anode catalyst layer material of the present invention synthesizes the precursor material by a sol-gel method, so that each element in the material is evenly distributed, and the synthesis method is simple and efficient.

[0018] The application of the direct methane solid oxide fuel cell anode catalyst layer material of the present invention will broaden the path of high-temperature catalytic hydrogen production from hydrocarbon fuels in solid oxide fuel cells, which is beneficial to the application of solid oxide fuel cell anode catalysis. By adding an anode catalyst layer with high catalytic activity for methane to the anode material, the direct contact between the solid oxide fuel cell (SOFC) anode and methane is reduced, the methane-steam reforming activity is increased, the carbon deposition problem is alleviated, and the operating stability of the solid oxide fuel cell (SOFC) is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 SrTi 0.9 Ni 0.1 O 3-δ (STN) and SrTi 0.9 Ru 0.1 O 3-δ (STR) XRD spectrum after calcination at 1000 °C in air atmosphere for 5 h and then naturally cooling to room temperature.

[0020] Figure 2 The XRD spectra of STN and STR were tested after they were treated in H2 atmosphere at 800℃ for 2 h and then cooled to room temperature naturally.

[0021] Figure 3 These are SEM images of STN and STR before and after reduction.

[0022] Figure 4 It is the hydrogen programmed temperature curve of STN and STR.

[0023] Figure 5 It is the reduced STN (r-STN), the reduced STR 0.05 (r-STR0.05), reduced STR (r-STR0.1), and reduced STR 0.15 (r-STR0.15) Performance test results of methane-H2O reforming at 450-650℃.

[0024] Figure 6 (a) The IP and IV curves of a single cell without a catalytic layer using H2 as fuel; (b) The IP and IV curves of a single cell without a catalytic layer using CH4-H2O as fuel; (c) The IP and IV curves of a single cell with an r-STR catalytic layer using H2 as fuel; (d) The IP and IV curves of a single cell with an r-STR catalytic layer using CH4-H2O as fuel.

[0025] Figure 7 The stability of SOFC without catalyst layer (a) and with r-STR catalyst layer (b) tested in CH4-H2O. DETAILED DESCRIPTION

[0026] The direct methane solid oxide fuel cell anode catalyst layer material of the present invention is obtained by calcining a precursor material in a reducing atmosphere. The molecular formula of the precursor material is SrTi 1-x Ru x O 3-δ , where 0.05≤x≤0.15 and δ is the oxygen vacancy content. By calcining a precursor material of a specific molecular formula in a reducing atmosphere, that is, by an in-situ precipitation strategy, nano-metal particles are "anchored" on the surface of the anode perovskite oxide substrate of a solid oxide fuel cell (SOFC). Due to the in-situ precipitation, the two phases are tightly bound, have high stability and sintering resistance, and significantly improve the catalytic activity and durability of the catalyst layer material; the nano-particles precipitated on the surface of the catalyst layer material increase the active sites, stimulate the mechanism of lattice oxygen participating in the reforming of methane, accelerate the methane reforming rate, and reduce the generation of carbon deposits. The calcination temperature is 720~820 ℃, and the calcination holding time is 2~5 h. x is preferably 0.1.

[0027] The preparation method of the direct methane solid oxide fuel cell anode catalyst layer material comprises the following steps: (a) weighing a corresponding proportion of a soluble strontium salt, a soluble ruthenium salt and an organic titanium compound according to the stoichiometric ratio of the precursor material molecular formula, adding them to water to dissolve and obtain a clear mixed solution; dissolving a complexing agent in an alkaline solution to form an alkaline regulating solution; then adding the alkaline regulating solution to the mixed solution, controlling the pH of the mixed solution to 9-10, heating and stirring to obtain a gel-like substance; (b) drying the gel-like substance and subjecting it to high-temperature heat treatment to obtain a precursor material; (c) calcining the precursor material in a reducing atmosphere to obtain the direct methane solid oxide fuel cell anode catalyst layer material. The precursor material is synthesized by the sol-gel method, so that each element in the material is evenly distributed, and the synthesis method is simple and efficient.

[0028] In step (a), the soluble strontium salt is Sr(NO3)2, the soluble ruthenium salt is RuCl3, the organic titanium compound is tetrabutyl titanate, the complexing agent is ethylenediaminetetraacetic acid, and the alkaline solution is 20-25% ammonia water by mass. In step (a), citric acid monohydrate is first added to water, the molar ratio of citric acid monohydrate, ethylenediaminetetraacetic acid and total metal ions is 2:1:0.5-1.5, and the total metal ions are strontium ions and ruthenium ions. In step (b), the drying treatment temperature is 150-200°C and the time is 5-10h. In step (b), the temperature of the high temperature heat treatment is 950-1000°C and the time is 5-8h. In step (c), the reducing atmosphere is H2 atmosphere.

[0029] The application of the above direct methane solid oxide fuel cell anode catalyst layer material is used as the catalyst layer on the anode side of the direct methane solid oxide fuel cell.

[0030] The present invention is further described in detail below in conjunction with specific examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. Example 1

[0031] This embodiment provides a direct methane solid oxide fuel cell (DM-SOFC) anode catalyst layer material, the precursor molecular formula of which is: SrTi 0.9 Ru 0.1 O 3-δ (STR), the specific preparation method is as follows: (a) According to SrTi 0.9 Ru 0.1 O 3-δ(STR) molecular formula stoichiometric ratio Weigh 15.314 g tetrabutyl titanate and 42.028 g CA (citric acid monohydrate) into a 3000 ml beaker and add 300 ml deionized water to dissolve, then add 0.582 g Sr(NO3)2 and 1.366 g RuCl3, then place the beaker on a stirring heating table and heat (temperature is 90°C) and stir until the solution is clear. Dissolve 29.224 g EDTA in 100 ml ammonia water, add to the above solution, adjust the pH of the solution to between 9 and 10, heat and stir to evaporate the water until a gel-like substance is obtained; (b) drying the gel-like substance prepared in step (a) at 180° C. for 5 h, and then calcining at high temperature (calcining at 1000° C. for 5 h) to obtain an anode catalyst layer material precursor; (c) The anode catalyst layer material precursor prepared in step (b) is heated to 800°C at a heating rate of 5°C / min in a H2 atmosphere, and is kept at this temperature for 2 hours to obtain a direct methane solid oxide fuel cell (DM-SOFC) anode catalyst layer material (i.e., reduced STR 0.1 , r-STR0.1). Example 2

[0032] This embodiment provides a direct methane solid oxide fuel cell (DM-SOFC) anode catalyst layer material, which is basically the same as that in Example 1, except that the amount of metal salt is adjusted so that the precursor molecular formula is: SrTi 0.95 Ru 0.05 O 3-δ The final catalyst material is STR after reduction 0.05 , that is, r-STR0.05. Example 3

[0033] This embodiment provides a direct methane solid oxide fuel cell (DM-SOFC) anode catalyst layer material, which is basically the same as that in Example 1, except that the amount of metal salt is adjusted so that the precursor molecular formula is: SrTi 0.85 Ru 0.15 O 3-δ The final catalyst material is STR after reduction 0.15 , that is, r-STR0.15.

[0034] Comparative Example 1 This comparative example adopts the sol-gel method to prepare the anode catalyst layer material of direct methane solid oxide fuel cell (DM-SOFC), which is basically the same as that in Example 1, except that Ni(NO3)3 is used instead of RuCl3. The specific preparation process is as follows: By SrTi0.9 Ni 0.1 O 3-δ 15.314 g of tetrabutyl titanate and 42.028 g of CA were weighed into a 3000 ml beaker and dissolved in 300 ml of deionized water. Then 0.582 g of Sr(NO3)2 and 1.454 g of Ni(NO3)3 were added. The beaker was placed on a stirring heating table and heated and stirred until the solution was clear. 29.224 g of EDTA was dissolved in 100 ml of ammonia water and added to the above solution. The pH of the solution was adjusted to between 9 and 10. The water was evaporated by heating and stirring until a gel-like substance was obtained. After being dried in a high-temperature oven, it was taken out and calcined again in a high-temperature muffle furnace (calcined at 1000°C for 5 hours) to obtain the precursor oxide SrTi 0.9 Ni 0.1 O 3-δ (STN) powder.

[0035] The STN powder was subjected to high-temperature reduction treatment in a tubular furnace (the high-temperature reduction treatment process was the same as in Example 1) to obtain an r-STN sample (ie, r-STN).

[0036] Figure 1 The X-ray diffraction (XRD) spectra of the precursor a region synthesized in Example 1 and Comparative Example 1 show that the samples in Example 1 of the present invention are all pure cubic perovskite phases and no characteristic peaks of other impurities are found, indicating that the doping of Ru cations does not change the crystal structure of the sample, but successfully enters the cubic perovskite lattice. In Comparative Example 1, STN has characteristic peaks of NiO, indicating that 10% Ni metal has not completely entered the strontium titanate perovskite.

[0037] Figure 2 The XRD spectra of the samples r-STR and r-STN after reduction in Example 1 and Comparative Example 1 are shown. The results show that both materials have Ni and Ru metal peaks, but their phase structures are still cubic perovskite phases. This indicates that the two materials maintain good stability after being treated in a reducing atmosphere.

[0038] Figure 3 The scanning electron microscope (SEM) images of Example 1 and Comparative Example 1. The SEM results show that both materials r-STN and r-STR are composed of two phases, including substrate perovskite STN and STR, and nanoparticles of Ni and Ru metal elements uniformly distributed on the perovskite substrate.

[0039] Figure 4This is the curve change analysis of STN and STR of Example 1 and Comparative Example 1 after high temperature programmed hydrogen reduction (H2-TPR) test in 10% H2-Ar atmosphere. Figure 4 The analysis found that the STN of Comparative Example 1 corresponds to the reduction of free NiO to Ni element, the reduction of bulk NiO bound to the perovskite substrate to Ni element, and the precipitation of Ni element from the perovskite lattice at about 290°C, 353°C, and 500°C, respectively. Compared with Comparative Example 1, the overall signal peak of STR in Example 1 is lower, and the signal peak begins to appear at about 200°C, which is consistent with the temperature at which Ru precipitates from the perovskite.

[0040] Comparative Example 2 This comparative example is used to compare the electrochemical performance and stability of a direct methane solid oxide fuel cell without adding an anode catalyst layer. The anode material composition is NiO mixed with Sm 0.2 Ce 0.8 O2 (SDC). The preparation and electrochemical performance test process of a single cell is as follows: Preparation of single cell: The single cell adopts an anode catalyst layer||Ni-SDC||SDC||cathode structure. The Ni-SDC anode support sheet is prepared by physical mixing and dry pressing. The mass ratio of NiO to SDC is 3:2 and pressed into a disc with a diameter of 15 mm. Subsequently, the SDC electrolyte material is evenly pressed on the anode support sheet. The half-cell after dry pressing is heated at 5°C / min in a muffle furnace and calcined at 1400°C for 5 hours. The cathode slurry Ba is sprayed on the electrolyte side of the calcined half-cell sheet 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ The cathode slurry was prepared by dissolving a certain amount of cathode powder in a mixed solution of appropriate amounts of isopropanol, ethylene glycol and glycerol. At the same time, a high-energy ball mill was used to ensure uniform dispersion of the cathode. The prepared single cell was calcined at 1000 °C for 2 hours in an air atmosphere. The anode catalyst layer r-STR slurry was also prepared using the above method and evenly sprayed on the anode side without calcination. The effective cathode area of ​​the battery is 0.45 cm 2 .

[0041] Electrochemical test: The prepared single cell was tested using a solid oxide fuel cell performance test device. CH4 20 mL / min, water vapor 20 mL / min, and air 80 mL / min were introduced into the anode side, and the cathode side was introduced into the cathode side. The electrochemical performance of the single cell was tested in the range of 450 ℃ to 650 ℃. Under this condition, the performance of the single cell was tested in the temperature range of 450 ℃ to 650 ℃ at intervals of 50 ℃, and the battery was subjected to an electrochemical impedance test.

[0042] The present invention tests the catalytic performance of the catalyst in the samples of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, and the test method is as follows: The catalyst needs to be granulated before testing so that it can be reacted and tested in a fluidized bed reactor. The process of catalyst granulation is as follows: weigh an appropriate amount of catalyst powder and pressurize it to form a solid flake; sieve a uniform catalyst with a particle size of 0.2 g through a 40-mesh to 60-mesh sieve; mix the obtained catalyst with quartz sand of the same particle size at a mass ratio of 1:2; after mixing, place it on a 0.2 g asbestos bed to ensure uniform particle distribution and effective active area of ​​the reaction. The catalyst preparation of the comparative material is the same as the above process. Next, the catalyst is loaded into the fluidized bed reactor, placed in a high-temperature furnace, and the furnace temperature is steadily raised to 800 °C. 50 mL / min of hydrogen is introduced and reduced for 2 hours. After the reduction is completed, the hydrogen is turned off, and 20 mL / min of methane and 20 mL / min of water vapor are introduced. The water vapor is vaporized by the vaporizer and fed in by a quantitative pump, and the liquid water is transported to the gas pipeline with a heating belt insulation by the carrier gas, and finally enters the reaction device. The catalytic reaction test temperature range of the catalyst is 450 to 650 °C, and a point is taken for testing every 50 °C. After the reaction, the product is dehydrated by a condensation device, and then quantitatively analyzed by chromatography to detect the product composition. The gas flow of the product is tested by a soap bubble flowmeter.

[0043] Figure 5 The results of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 in testing the catalytic performance of the catalyst. r-STN has almost no catalytic activity in the range of 450 ℃ to 650 ℃. In contrast, the catalytic efficiency of r-STR0.1 at 650 ℃ reached 39.2%, which is much higher than r-STR0.05 and r-STR0.15, indicating that 10 mol% Ru substitution at the B position is the optimal doping content in ST, and the overall catalytic activity is higher than that of the anode material. The difference in catalytic efficiency between r-STN and r-STR may be due to the different particle morphology of the precipitated metal and the influence of the metal itself on the SMR catalytic mechanism.

[0044] Figure 6 The electrochemical performance test results of Example 1 and Comparative Example 2 are shown in Figure 2. The power density of a single cell containing an r-STR catalyst layer under CH4-H2O conditions at 650°C, 600°C, 550°C, 500°C and 450°C is 1232 mW / cm 2 、806mW / cm 2 、404mW / cm 2 、164mW / cm 2 and 54 mW / cm 2Under the same conditions, the power density of a single cell without a catalytic layer is 913 mW / cm 2 、604mW / cm 2 、318mW / cm 2 、131mW / cm 2 and 44 mW / cm 2 The test results show that as the temperature increases, the performance of a single cell containing an r-STR catalyst layer improves significantly more than that of a cell without a catalyst layer. The reason is that the SMR reaction is an endothermic reaction, and the conversion rate increases as the temperature rises. At the same time, the further improvement of the catalyst layer also improves the conversion efficiency, thereby improving the battery performance.

[0045] Figure 7 The stability test of the battery of Example 1 and Comparative Example 2. At a constant current density (200 mA·cm) with a CH4:H2O flow ratio of 1:1 -2 ) During operation, the operating voltage of the SOFC containing the STR anode catalyst layer increases slowly from 0 to 60 h. The reason for this phenomenon is that the Ru nanoparticles slowly precipitate from the STR, resulting in a gradual increase in the SMR catalytic activity. After more than 60 h, the operating voltage of the battery slowly decreases and then stabilizes. This may be due to the gradual coarsening of the Ru nanoparticle catalyst in the catalyst layer and the gradual stabilization of the catalytic activity. However, for the SOFC without a catalyst layer, the operating voltage of the battery decays significantly and rapidly when operating at the same current density and fuel. This rapid decay may be due to the direct contact between the anode and methane in the absence of a catalyst layer, resulting in carbonization of the nickel-based anode surface area, thereby blocking the anode active sites and causing the SMR catalytic activity to gradually decrease.

[0046] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A direct methane solid oxide fuel cell anode catalyst layer material, characterized in that: It is obtained by calcining a precursor material in a reducing atmosphere. The molecular formula of the precursor material is SrTi 1-x Ru x O 3-δ , where 0.05≤x≤0.15 and δ is the oxygen vacancy content.

2. The direct methane solid oxide fuel cell anode catalyst layer material according to claim 1, characterized in that: The calcination temperature is 720-820°C and the calcination holding time is 2-5 hours.

3. The direct methane solid oxide fuel cell anode catalyst layer material according to claim 1 or 2, characterized in that: x is preferably 0.

1.

4. The method for preparing the direct methane solid oxide fuel cell anode catalyst layer material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (a) weighing a soluble strontium salt, a soluble ruthenium salt and an organic titanium compound in a corresponding proportion according to the stoichiometric ratio of the molecular formula of the precursor material, adding the mixture into water and dissolving the mixture to obtain a clear mixed solution; dissolving the complexing agent in an alkaline solution to form an alkaline regulating solution; Then, the alkaline regulating solution is added to the mixed solution, the pH value of the mixed solution is controlled to be 9-10, and the mixed solution is heated and stirred to obtain a gel-like substance; (b) drying the gel-like substance and subjecting it to high-temperature heat treatment to obtain a precursor material; (c) placing the precursor material in a reducing atmosphere to calcine to obtain the direct methane solid oxide fuel cell anode catalyst layer material.

5. The method for preparing the anode catalyst layer material of direct methane solid oxide fuel cell according to claim 4, characterized in that: In step (a), the soluble strontium salt is Sr(NO3)2, the soluble ruthenium salt is RuCl3, the organic titanium compound is tetrabutyl titanate, the complexing agent is ethylenediaminetetraacetic acid, and the alkaline solution is ammonia water with a mass fraction of 20-25%.

6. The method for preparing the anode catalyst layer material of direct methane solid oxide fuel cell according to claim 5, characterized in that: In step (a), citric acid monohydrate is first added to water, the molar ratio of the citric acid monohydrate, ethylenediaminetetraacetic acid and total metal ions is 2:1:0.5-1.5, and the total metal ions are strontium ions and ruthenium ions.

7. The method for preparing the anode catalyst layer material of direct methane solid oxide fuel cell according to claim 4, characterized in that: In step (b), the drying treatment temperature is 150-200° C. and the time is 5-10 hours.

8. The method for preparing the anode catalyst layer material of direct methane solid oxide fuel cell according to claim 7, characterized in that: In step (b), the high temperature heat treatment is performed at a temperature of 950-1000° C. and a time of 5-8 hours.

9. The method for preparing the anode catalyst layer material of direct methane solid oxide fuel cell according to claim 4, characterized in that: In step (c), the reducing atmosphere is a H2 atmosphere.

10. The use of the direct methane solid oxide fuel cell anode catalyst layer material according to any one of claims 1 to 3, characterized in that: It is used as the catalytic layer on the anode side of direct methane solid oxide fuel cells.

Citation Information

Patent Citations

  • Multi-stage structure composite fuel electrode for solid oxide electrolytic tank and preparation method thereof

    CN113832495A

  • High-performance anti-carbon-deposition solid oxide fuel cell anode structure, cell and application

    CN116565222A

  • Catalyst for methane reforming and method for producing same

    CN116635145A

  • Direct ammonia proton fuel cell anode functional layer material and preparation method and application thereof

    CN117199408A